HIV is still a major public health problem among pregnant women attending ANC in Referral Hospitals of the Amhara Regional State, Ethiopia: a cross sectional study - Workie Zemene Worku; Telake Azale; Tadesse Awoke Ayele; Dawit Kassahun Mekonnen (BMC, 2022)
Plain language Millions lost their lives for HIV/AIDS while many more live with the virus with significantly compromised degree of quality of life. Women are more affected than men because of various contributing factors. This study was aimed to determine the proportion and associated factors of HIV status among pregnant women attending ANC at referral hospitals of the Amhara Regional State, Ethiopia. The study was conducted from October 2020 to December 2020. A total of 538 pregnant women were included in the study selected from three referral hospitals.  An interviewer-administered questionnaire was used to collect the data. A binary logistic regression analysis was used to identify the association between factors of the study participants and HIV status. The result revealed that the overall proportion of HIV among pregnant women was 8.68%. Women who completed secondary education, graduated from higher education and having a relatively adequate monthly income were found to have less chance of contracting HIV. On the other hand, pregnant women who had history of previous abortion and positive for syphilis had a higher chance to be infected with HIV. Such a high HIV proportion among the participants in the study area implies that there might be lack of awareness about HIV infection transmission methods as well as HIV prevention and control strategies. In this connection, behavior change intervention strategy prepared specifically for women is recommended to reduce their vulnerability. Besides promoting the use of family planning methods to reduce unsafe abortions and syphilis as well as regular screening and testing for syphilis are important to consider.